Antifungal Action of Ozone on Chicken Eggshell Cuticles: A Preliminary Study. (4th July 2022) - Soares, Carlos Eduardo Da Silva; Eduardo Cartabiano Leite, Cláudio; Dahlke, Fabiano; Maiorka, Alex; Miotto, Marília; Scussel, Vildes; De Dea Lindner, Juliano
ABSTRACT: Ozone gas (O3 ) is used as an oxidizing agent and can be applied as a sanitizer to control microorganisms and degrade toxic compounds, such as pesticides and mycotoxins, in food industries. Some studies investigated the use of O3 as an agent to reduce pathogenic bacteria such as Salmonella enteritidis . The action of O3 on the eggshell cuticle and structures of filamentous fungi is still not yet well studied. In this work, scanning electron microscopy (SEM) was used to assess the hens' eggshell structure after the exposition to O3, mainly to obtain information about the potential antifungal action. The SEM micrographs obtained shown that the application of O3 during 120 min damaged fungi hyphae adhered to the eggshell cuticle without severely compromising the external structure of the eggshell. Further studies are necessary to establish an ideal O3 treatment for the fungal decontamination of chicken eggs.